A case of acute brucellosis with pericardial involvement - Demirda, Kutbettin; Ozden, Mehmet; Ozbay, Lmaz; Yuce, Pinar; Kalkan, Ahmet (Aves, 2005)
Brucellosis, an endemic disease in our region, is among the most common zoonotic infections in the world. Cardiovascular involvement is a rare complication of the disease and it frequently involves endocarditis. Pericarditis usually develops as the complication of endocarditis although primary pericarditis can rarely develop. In this study, a 50-year old woman with brucellosis case who developed pericardial effusion was presented. The patient was admitted to our hospital with a history of fever, sweating, chest pain, dyspnea, tachycardia, and malaise for 45 days. Wright agglutination test (STA) was 1/160 and Brucella melitensis yielded in the blood culture. The case was initiated the rifampicine 600 mg/day and doxycycline 200 mg/day. The complaints decreased on the 5th day of the treatment and the pericaridal fluid was determined to diminish in echocardiography. The clinical and laboratory findings of the case recovered in post-treatment follow-up, and the pericardial fluid was measured to be within the physiological values. In conclusion, brucellosis should be kept in mind in the etiology of the pericardial effusion in the regions where brucellosis is endemic.
Keywords: Brucellosis; pericardial effusion